DIFFERENCES IN DEBRIS INDEX AND pH SALIVABEFORE AND AFTER CONSUMING WATERMELON FRUIT (CITRULLUS LANATUS) IN GRADE 4 STUDENTS OF MI DARUSSALAM JAMBI CITY - Idham Halid; Junaidi Junaidi (Poltekkes Kemenkes Jambi, 2020)
Background: Debris is a soft layer of food remnants, attached not tightly to the surface of the teeth, can be seen a few minutes after finishing the meal. If we do not brush our teeth in 1 day of course debris accumulates on the surface of the teeth. Watermelon fruit has high water content, high fiber and vitamin C so it is expected that consuming watermelon fruit can reduce debris buildup and affect saliva pH. The purpose of this study was to find differences in debris index and ph saliva before and after consuming watermelon fruit. Method: This was an ex-perimental design (experimental research) that is an experimental activity that aims to find out a symptom / influence due to the existence of certain treatments (consuming watermelon fruit). In this study, the population was students of Madrasah Ibtidaiyah Darussalam with a sample of 34 students in grade IV. Results:there are significant differences in the debris index before and after consuming watermelon fruit. There is no significant difference in pH saliva before and after consuming watermelon fruit. There was no significant difference in the debris index in the treatment group with the debris index control group after consuming watermelon fruit. There was no significant difference in pH Saliva in the treatment group with pH Saliva control group after consuming watermelon fruit in students kela IV MI Darussalam Jambi City . Conclusion: there are significant differences in debris scores before and after consuming watermelon fruit.